2023
DOI: 10.3390/chemosensors11050271
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Deactivation of Mesoporous Co3O4-Supported Au–Pd Catalyst through Gas Sensor Operation

Abstract: High activity of a catalyst and its thermal stability over a lifetime are essential for catalytic applications, including catalytic gas sensors. Highly porous materials are attractive to support metal catalysts because they can carry a large quantity of well-dispersed metal nanoparticles, which are well-accessible for reactants. The present work investigates the long-term stability of mesoporous Co3O4-supported Au–Pd catalyst (Au–Pd@meso-Co3O4), with a metal loading of 7.5 wt% and catalytically active mesoporo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…reported that three-dimensionally ordered, mesoporous Co 3 O 4 is not appropriate for application in pellistors due to the high instability of its structure under pellistor operation conditions. Especially, the mesoporous Co 3 O 4 catalyst functionalized with Au-Pd nanoparticles exhibited strong deactivation because of strong metal oxide sintering [ 32 ]. Thus, the suitable structure and morphology of the metal oxide had a crucial impact on performance of the catalytic sensors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that three-dimensionally ordered, mesoporous Co 3 O 4 is not appropriate for application in pellistors due to the high instability of its structure under pellistor operation conditions. Especially, the mesoporous Co 3 O 4 catalyst functionalized with Au-Pd nanoparticles exhibited strong deactivation because of strong metal oxide sintering [ 32 ]. Thus, the suitable structure and morphology of the metal oxide had a crucial impact on performance of the catalytic sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the suitable structure and morphology of the metal oxide had a crucial impact on performance of the catalytic sensors. Despite the high interest in metal oxides as catalysts for catalytic combustion, metal oxide materials have hardly been tested for use in catalytic gas sensors [ 32 , 33 ]. Although the catalytic oxidation of target gases underlies the sensor’s response, the results of standard catalyst studies using reactors cannot be easily transferred to catalytic gas sensors because the catalysts are prepared for examination according to the requirements for the catalytic bed reactors, e.g., by dilution with other components, pelletization, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The basis experimental investigations were performed on spinel cobalt oxide (Co 3 O 4 ) catalyst because previous works showed its high stability which is important for correct method evaluation. Moreover, Co 3 O 4 with variable valence states (Co 2+ /Co 3+ ) has attracted increasing attention as a very active non-noble metal catalyst for the catalytic combustion of CH 4 2 , 10 or as a support for noble metal catalyst 37 . With the focus on the sensor application, the temperature range between 250 and 450 °C was chosen for the investigations.…”
Section: Introductionmentioning
confidence: 99%